Investigating the Vocabulary Level on Mispronunciation among Eighth-Grade Students in SMPN 11 Bekasi - Dama Tantisari; Sulhizah Wulan Sari; Eleena Putri Reevenza; Jasmine Kayla Az-Zahra; Rindianti Jasmine Azzahra; Pratiwi Aisyah Febriani; Tigana Novsya (Lembaga Penelitian dan Pengabdian kepada Masyarakat dan Program Studi Pendidikan Bahasa Inggris Fakultas Bahasa dan Seni Universitas Negeri Jakarta, 2025)
This article aimed at identifying the student’s vocabulary level from the phonetic transcription of students’ mispronunciations. A descriptive qualitative method was used in this study by taking an interview, audio, and video recording of the pronunciation of eighth-grade students in State Junior High School 11 Bekasi. The sample data was taken randomly with representative sampling. The findings indicated that the student's ability to pronounce vocabulary was at an easy level (92, 5%). They were able to pronounce familiar vocabularies used in daily conversation such as bag, teacher, and classroom. Conversely, the medium and high levels were challenging to pronounce since the vocabularies were presented in the scientific text. The inaccuracy in articulation was caused by the lack of familiarity with the sounds of vowels and consonants. This study was significant to be conducted for effective communication and pronunciation development on how individuals and teachers can apply the fundamentals of phonemics sound by correcting and preventing mispronunciations.